Multivitamin intake and the risk of congenital heart defects: A cohort study. (November 2022) - Taagaard, Mille; Trap Wolf, Hanne; Pinborg, Anja; Huusom, Lene Drasbek; Høgh, Stinne; Kvist Ekelund, Charlotte; Kristine Hegaard, Hanne; Rode, Line
Abstract: Objective: Congenital heart disease (CHD) is the most common type of congenital birth defect, but little is known about possible modifiable behavioral risk factors. The study aimed to assess whether intake of periconceptional or postconceptional multivitamin was associated with a decreased risk of CHD in the offspring. Study Design: The study population comprised 15, 567 women from the Copenhagen Pregnancy Cohort with complete data on multivitamin intake before and during pregnancy, who gave birth to live-born singletons from October 2012 to October 2016. Main outcome measure was CHD defined according to the International Classification of Diseases (ICD), 10th revision. Cases of CHD were classified into five subgroups based on the clinical phenotype: 1) Conotruncal defects, 2) Left ventricular outflow tract obstruction, 3) Right ventricular outflow tract obstruction, 4) Septal defects, and 5) Other CHD. Multivariate logistic regression analyses were performed with adjustment for maternal age, chronic disease, assisted reproductive technology, smoking status, and alcohol consumption. Results: Of the 15, 567 included women, 31.9 % reported a daily multivitamin intake in the periconceptional period, 53.7 % in the postconceptional period, and 14.4 % women did not report a daily multivitamin intake. The prevalence of CHD in the population was 0.7 % (n = 112). Periconceptional and postconceptional multivitamin intake was not associated with risk of overall CHD in offspring: Adjusted OR was 0.64 (95 % CI 0.36–1.13) and 0.77 (95 % CI 0.47–1.30), respectively. Conclusion: The current large cohort study did not show a preventive effect of multivitamin intake in the periconceptional or postconceptional period on the risk of CHD in the offspring.